Patient exposure and diagnostic reference levels in operating rooms: a multi-centric retrospective study in over 150 private and public French clinics. (22nd September 2020) - Farah, J; Gonzalez-Mendez, L A; Dufay, F; Amir, S; Royer, B; Gabriel, H; Noel, A
Abstract: To investigate patient exposure in operating rooms and establish diagnostic reference levels (DRLs), 15 different procedures and nearly 4500 surgeries performed between January 2017 and December 2019 at over 150 different private (79% of data) and public (21% of data) French clinics were recorded. Collected information include the used C-arm equipment, exposure parameters (kVp, mAs, Fluoroscopy Time—FT and Air Kerma-Area Product—PKA ) and patient body mass index whenever available. Multi-centric DRLs were derived as the 75th percentile of the median exposure data collected in more than ten different hospitals. For the less frequent procedures, DRLs were determined as the 75th percentile of pooled exposure data with a minimum of 4 centres and 100 patients. Patient exposure proved to be significantly different among the centres. Highest DRLs were found for Abdominal Aortic Aneurysm Endoprosthesis (18 min, 81 Gy cm 2 ), Iliac Angioplasty (6 min, 24 Gy cm 2 ) and Flutter Ablation surgeries (17 min, 14 Gy cm 2 ). In opposition, lowest DRLs were obtained for Hallux Valgus (0.4 min, 0.04 Gy cm 2 ), Hand/Wrist Fracture (0.6 min, 0.16 Gy cm 2 ), and Venous Access Device Implantation surgeries (0.3 min, 0.36 Gy cm 2 ). Similar exposure levels are registered in private clinics and public hospitals. Multi-centric DRLs for 15 surgical procedures including six new reference values were established to help optimise patients' radiation protection.